IMPLEMENTASI INFOGRAFIS PADA VIDEO BASIC MACHINE OPERATION MSP PT. INFINEON TECHNOLOGIES BATAM - Getha Febriyani Putri; Sandi Prasetyaningsih; Reisya Amelia (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2020)
As a form of education on the process of operating a machine or facility to support a job, PT. Infineon Technologies Batam utilizes multimedia technology as a medium for delivering information to employees to better understand how the work process and how to operate the machine to be used. Multimedia used is video media, which contains the production process of the industry. One of the videos that will be produced, the MSP basic machine operation video which is targeted at operator employees in the MSP area (mark, scan, pack), is the final process in making semiconductor products. The product produced in this thesis is the implementation of infographics on the video, using the action research completion method as a form of reflection by considering coloring and typography, so that the employees of PT. Infineon Technologies Batam can understand the video delivered quickly and easily. This video will be used as a training media for new employees who do not understand the process and how the machine works and can be used as a reference for all employees at PT. Infineon Technologies Batam